ICE STORAGE CHARACTERISTICS OF PERCH WITH SPECIAL REFERENCE TO ITS SUITABILITY FOR CANNING. - SOLANKI, K K; RADHAKRISHNAN, A G; JOSEPH, JOSE; VENKATARAMAN, R (Fishery Technology, 2017)
Perch (Pagrus spinifer), one of the most abundantly availablefishes of Gujarat coast, was subjected to a detailed studyfor assessing its storage life in ice and amenability of the icedfish for canning. Changes in the salt soluble nitrogenous materialand myosin content of the iced fish showed good correlationwith the changes in the organoleptic and physical qualities.The fish was found to have a storage life of 9 days in ice andsamples stored upto 7 days were suitable for canmng.